Global Distribution of O Serotypes and Antibiotic Resistance in Extraintestinal Pathogenic Escherichia coli Collected From the Blood of Patients With Bacteremia Across Multiple Surveillance Studies. (10th June 2022) - Weerdenburg, Eveline; Davies, Todd; Morrow, Brian; Zomer, Aldert L; Hermans, Peter; Go, Oscar; Spiessens, Bart; van den Hoven, Thijs; van Geet, Gunter; Aitabi, Moussa; DebRoy, Chitrita; Dudley, Edward G; et al.
Abstract: Background: Extraintestinal pathogenic Escherichia coli (ExPEC) is the leading cause of bacteremia worldwide, with older populations having increased risk of invasive bacterial disease. Increasing resistance to first-line antibiotics and emergence of multidrug-resistant (MDR) strains represent major treatment challenges. ExPEC O serotypes are key targets for potential multivalent conjugate vaccine development. Therefore, we evaluated the O serotype distribution and antibiotic resistance profiles of ExPEC strains causing bloodstream infections across 4 regions. Methods: Blood culture isolates from patients aged ≥60 years collected during 5 retrospective E. coli surveillance studies in Europe, North America, Asia-Pacific, and South America (2011–2017) were analyzed. Isolates were O serotyped by agglutination; O genotyping was performed for nontypeable isolates. Antimicrobial susceptibility testing was also conducted. Results: Among 3217 ExPEC blood culture isolates, the most ubiquitous O serotype was O25 (n = 737 [22.9%]), followed by O2, O6, O1, O75, O15, O8, O16, O4, O18, O77 group, O153, O9, O101/O162, O86, and O13 (prevalence of ≥1%). The prevalence of these O serotypes was generally consistent across regions, apart from South America; together, these 16 O serotypes represented 77.6% of all ExPEC bacteremia isolates analyzed. The overall MDR frequency was 10.7%, with limited variation between regions. Within the MDR subset (n = 345), O25 showed a dominant prevalence of 63.2% (n = 218). Conclusions: Predominant O serotypes among ExPEC bacteremia isolates are widespread across different regions. O25 was the most prevalent O serotype overall and particularly dominant among MDR isolates. These findings may inform the design of multivalent conjugate vaccines that can target the predominant O serotypes associated with invasive ExPEC disease in older adults. Abstract : Extraintestinal pathogenic Escherichia coli (ExPEC) is the leading cause of bacteremia worldwide, and O serotypes are key vaccine targets. We determined O serotype prevalence among ExPEC bacteremia isolates from elderly patients and found global dominance of O serotype O25B, particularly among multidrug-resistant isolates.